2019
DOI: 10.1093/intimm/dxz048
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic adaptation to glycolysis is a basic defense mechanism of macrophages for Mycobacterium tuberculosis infection

Abstract: HIF-1 induces LDH to decrease pyruvate in Mtb-infected macrophages

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 34 publications
8
52
0
Order By: Relevance
“…Causally linking the two, treatment of BMDMs with the glucose uptake inhibitor 2-deoxyglucose (2-DG) abrogated the reduction in bacillary burden conferred by IFN-γ. This mechanistic analysis was supported by in vivo studies showing that whole-body HIF-1α −/− mice are more susceptible to TB (Braverman et al, 2016 ), and this was later enhanced by two studies showing that myeloid-specific conditional HIF-1α knockout mice are also more susceptible to TB (Osada-Oka et al, 2019 ; Resende et al, 2020 ). One of these studies also indicated that the transcription of lactate dehydrogenase A was controlled by HIF-1α in Mtb infected BMDMs independent of INF-γ, and demonstrate that HIF-1α reduces the pyruvate levels in the macrophages, which is used as a preferable source for intracellular Mtb replication over glucose (Osada-Oka et al, 2019 ).…”
Section: The Warburg Effect In Tb: Macrophage Functionsmentioning
confidence: 94%
See 3 more Smart Citations
“…Causally linking the two, treatment of BMDMs with the glucose uptake inhibitor 2-deoxyglucose (2-DG) abrogated the reduction in bacillary burden conferred by IFN-γ. This mechanistic analysis was supported by in vivo studies showing that whole-body HIF-1α −/− mice are more susceptible to TB (Braverman et al, 2016 ), and this was later enhanced by two studies showing that myeloid-specific conditional HIF-1α knockout mice are also more susceptible to TB (Osada-Oka et al, 2019 ; Resende et al, 2020 ). One of these studies also indicated that the transcription of lactate dehydrogenase A was controlled by HIF-1α in Mtb infected BMDMs independent of INF-γ, and demonstrate that HIF-1α reduces the pyruvate levels in the macrophages, which is used as a preferable source for intracellular Mtb replication over glucose (Osada-Oka et al, 2019 ).…”
Section: The Warburg Effect In Tb: Macrophage Functionsmentioning
confidence: 94%
“…This mechanistic analysis was supported by in vivo studies showing that whole-body HIF-1α −/− mice are more susceptible to TB (Braverman et al, 2016 ), and this was later enhanced by two studies showing that myeloid-specific conditional HIF-1α knockout mice are also more susceptible to TB (Osada-Oka et al, 2019 ; Resende et al, 2020 ). One of these studies also indicated that the transcription of lactate dehydrogenase A was controlled by HIF-1α in Mtb infected BMDMs independent of INF-γ, and demonstrate that HIF-1α reduces the pyruvate levels in the macrophages, which is used as a preferable source for intracellular Mtb replication over glucose (Osada-Oka et al, 2019 ). However, this study supports previous findings (Braverman et al, 2016 ) that the treatment of BMDMs with IFN-γ induces a greater increase in the secreted lactate levels and further reduces the bacillary loads than that observed in untreated BMDMs (Osada-Oka et al, 2019 ).…”
Section: The Warburg Effect In Tb: Macrophage Functionsmentioning
confidence: 94%
See 2 more Smart Citations
“…In this respect, apart from host immune cells using their metabolism to initiate host defense responses, also pathogens are able to exploit these host metabolic pathways for their own benefit. On the one hand, they tap into these pathways to acquire nutrients and macromolecules that directly promote their own survival and replication [8][9][10][11][12][13][14][15]. On the other hand, it is now becoming clear that pathogens also manipulate metabolic pathways of host innate immune cells, to modulate, dampen, or evade the immune responses to further enhance their chances of survival.…”
Section: Introductionmentioning
confidence: 99%